Clinical data related to breast reconstruction; looking back on the 21th century and forward to the next steps - Jecan Cristian Radu; Hernic Alexandru Daniel; Filip Iulia Cristina; Răducu Laura (Journal of Mind and Medical Sciences)
Breast reconstruction after breast cancer surgery represents a positive step in restoring a women’s idea of self by reestablishing her feminine features and confidence, thus improving essential aesthetic and emotional aspects. Regarded as the cornerstone in breast cancer management, the surgical treatment has come a long way since 1884 when W.S. Halsted performed the first radical mastectomy- a disfiguring procedure which was conducted until the late 70s when owing to contemporary advancements it was surpassed by modified radical mastectomies and other far less invasive approaches. Either performed in an immediate or a delayed fashion breast reconstruction can be achieved not only through alloplastic procedures using expander/ implant prosthesis but also through autologous tissue transfers wisely harvested from different parts of the body or through methods that combine the two. When planning a breast reconstruction, after the oncologist formally rules out any form of residual cancer, one must take into consideration several critical factors that will eventually condition the technique election process for example the possible local or systemic adjuvant therapy. Although a “one size fits all” breast reconstruction procedure has yet to prevail, the extensive volume of published literature regarding this matter enables a well-experienced plastic surgeon to proceed with careful procedural selection allowing for the best possible results.